Oil palm biomass reinforced palm oil-based polyurethane composite foam and its structural sandwich - Teo, Siew Cheng (School of Materials Engineering, 2016)
This research is aimed to find the value of the oil palm biomass by applied them as reinforcement in composite foam that derived from palm oil-based polyurethane. The oil palm-based composite foam is further applied as a sandwich core in a structural sandwich. To achieve the overarching aim, the objectives are defined below; to investigate the single fibre strength of empty fruit bunch fibre and its interfacial strength to various polymer matrices in unidirectional fibre composites; to determine the effect of empty fruit bunch content on the mechanical properties of empty fruit bunch fibres reinforced palm oil-based polyurethane composite foam and its structural sandwiches; to verify the effect of DPS - PKS palm shells blend ratio and its content in conjunction with the effect of empty fruit bunch fibres content on the mechanical properties and weathering behaviour of oil palm biomass reinforced palm oil- based polyurethane composite foams and their sandwich structure.